How do we know who we are when we’re online? Reputation, identity, and influence in scholarly networks - Stewart, Bonnie (Proceedings of the International Conference on Networked Learning, 2014)
This short paper outlines an ethnographic project exploring how influence, reputation, and academic identity are circulated and enacted within scholarly online networks. Both academia and social networks can be said to be ‘reputational economies’ (Willinksy, 2010), but while scholars and educators are increasingly exhorted to ‘go online,’ those who do often find that their work and efforts may not be visible or understood within institutional contexts. This project utilizes ethnographic methods and a material-semiotic theoretical approach to explore and detail the ways in which networked scholarly reputations operate, circulate, and intersect with contemporary concepts of academic impact. The study aims to articulate the signals which ‘count’ towards influence and scholarly reputation in networked circles, and to explore the benefits and challenges that networked scholarly participation poses for contemporary academics who engage in it. Research into computer-based interactions has, for decades, suggested that online group members develop signals for status and credibility: Walther (1992) found “electronic communicators have developed a grammar for signalling hierarchical positions” (p. 78). More recently, Kozinets (2010) framed this status differentiation less in terms of hierarchy than “various strategies of visibility and identity expressions” (p. 24). Literature on networked scholarship is growing but has not as yet delved deeply into questions of how networked reputations, credibility, and status positions are produced, nor what implications these hold for conventional academic practices. This research investigates reputational strategies and practices within networked publics from a new literacies perspective, as a form of networked learning with the ethos of participatory culture. The paper explores the contexts, understandings, learning processes, and mediating technologies that have contributed to the development of participants’ outlooks and specific practices. Likewise, it also frames those practices and outlooks in relation to multiple circulating concepts of influence that intersect within academic networks. Through interviews and extensive participant observation within scholarly online networks, this project explores how interactions within scholarly networked publics intersect with conventional notions of academic identity, and offers a snapshot of the various ways in which online networks open up new possibilities for scholarly engagement, learning, identity expression and influence that may not be visible, legible, or available within the academy.